ANALISIS PARAMETER KEGEMPAAN (NILAI-a DAN NILAI-b) DI WILAYAH BUSUR BANDA - Shofiyatul Mahmudah; Zainul Arifin Imam Supardi (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Some areas in Indonesia are earthquake-prone areas, one of which is the Banda arc. The Banda arc has a complete tectonic system and is also an area with a high level of seismicity. One of the earthquake disaster mitigation efforts is by analyzing the a-values and b-values which are seismotectonic parameters. The a-values and b-values can be analyzed through the Gutenberg-Ritchter equation through the frequency-magnitude distribution. The gradient of the frequency-magnitude distribution is the b-value which is a stress distribution constant which indicates the level of fragility of the rocks in the area, while the a-value indicates seismic activity which is the seismicity constant. In determining the a-value and b-value depends on the Magnitude completeness (Mc). This study uses earthquake data from the USGS catalog from 2015–2020 and then uniformizes the magnitude to magnitude moment (Mw), declusters the earthquake catalog to eliminate the effects of foreshocks and aftershock to obtain the main earthquake data through ZMAP 6.0 software. After that, do a magnitude-frequency distribution plot to determine the completeness of the data in order to obtain the completeness of magnitude (Mc) which can be used to determine the a-value and b-value using ZMAP 6.0 software. The result of this research is the value of Magnitude Completeness (Mc) is 4.5, while the a-value is 9,07 and the b-value is 1,33. For the spatial variation of a-values and b-values, there are areas with a low a-value of 7 and a low b-value of 1,2 which have a chance of a large earthquake in the future due to the accumulation of energy that causes a high level of stress in the area.